A Quantum Chemical Interpretation of Two-Dimensional Electronic Spectroscopy of Light-Harvesting Complexes - Segatta, Francesco; Cupellini, Lorenzo; Jurinovich, Sandro; Mukamel, Shaul; Dapor, Maurizio; Taioli, Simone; Garavelli, Marco; Mennucci, Benedetta (Journal of the American Chemical Society, 2017)
Nonlinear electronic spectroscopies represent one of the most powerful techniques to study complex multichromophoric architectures. For these systems, in fact, linear spectra are too congested to be used to disentangle the many coupled vibroelectronic processes that are activated. By using a 2D approach, instead, a clear picture can be achieved, but only when the recorded spectra are combined with a proper interpretative model. So far, this has been almost always achieved through parametrized exciton Hamiltonians that necessarily introduce biases and/or arbitrary assumptions. In this study, a first-principles approach is presented that combines accurate quantum chemical descriptions with state-of-the-art models for the environment through the use of atomistic and polarizable embeddings. Slow and fast bath dynamics, along with exciton transport between the pigments, are included. This approach is applied to the 2DES spectroscopy of the Light-Harvesting 2 (LH2) complex of purple bacteria. Simulations are extended over the entire visible-near-infrared spectral region to cover both carotenoid and bacteriochlorophyll signals. Our results provide an accurate description of excitonic properties and relaxation pathways, and give an unprecedented insight into the interpretation of the spectral signatures of the measured 2D signals.